Successful Implementation of Continuous Glucose Monitoring in an Internal Medicine Residency Community Continuity Clinic in Patients with Diabetes Mellitus - Andrey Manov; Sukhjinder Chauhan; Gundip Dhillon; Athena Dhaliwal; Sabrina Antonio; Yema Jalal; Ashrita Donepudi; Jonathan Nazha; Melissa Banal; Joseph House (Disease and Health Research: New Insights Vol. 8, 2024)
Diabetes mellitus (DM) is the leading cause of blindness, non-traumatic amputation, and end-stage renal disease in the US. Continuous Glucose Monitoring (CGM) is an advancement in diabetes technology that continuously and automatically tracks blood glucose throughout the day and night. Continuous glucose monitoring (CGM) devices help people to manage diabetes with fewer fingerstick checks. Learning how to use a CGM takes time, but it can help more easily manage a diabetic patient’s health. Using a CGM device can make it easier to manage diabetes. Several studies show that people with Type 1 and Type 2 diabetes who use a CGM have fewer episodes of low blood sugar and a lower A1C. When combined with proper education, follow-up, and support, CGM has proven effective at improving the management of insulin-dependent diabetics. Our study aims to implement CGM in a resident-run internal medicine clinic, not specialized in endocrinology, to improve the quality of care for diabetic patients using 3-4 insulin injections daily. This was a retrospective observational cohort study that lasted one and a half years. Despite the bias related to individual patients’ adherence to diet, exercise, and other lifestyle interventions, the study aimed to evaluate the improvement of glucose control with CGM in a clinic run primarily by internal medicine residents under the supervision of an endocrine specialist. The role of the endocrinologist was mostly prominent in educating the residents initially on how to manage the patients using CGM. After that, the Internal Medicine residents worked autonomously in calling the patients, obtaining their CGM information, and adjusting based on it patient’s treatment of diabetes mellitus. Methods: Twenty-five patients at the Internal Medicine Residency Clinic with Type 1 or Type 2 DM on at least 3-4 insulin injections were provided with a CGM Dexcom 6 device and assigned to a resident who assesses their glucose management and subsequently adjusts their treatment regimens on a biweekly basis after consultation with board Certified Endocrinologist. Data were collected from the Dexcom Clarity database and the clinic EHR to assess changes in the following endpoints before and after implementation of CGM: average Hba1c/glucose management indicator (GMI), blood glucose, the incidence of low blood glucose (55-70 mg/dL), the incidence of very low blood glucose (<54 mg/dL), percent time in range (70-180 mg/dL), and satisfaction measures on quality of life questionnaire. Results: Average Hba1c/GMI was reduced to 7.04% from 11.21%, average blood glucose decreased to 158 mg/dL from 286 mg/dL, and incidence of low blood glucose < 70 mg/dl was reduced to 11 minutes per day from 1 hour and 14 min per day, the incidence of very low blood glucose less than 54 mg/dl was reduced to 3 minutes per day from 29 minutes per day, and time in range increased to 74% per day from 18%. A questionnaire given to patients after they started CGM also showed an improvement in their quality of life compared to self-monitoring blood glucose. Furthermore, 16% of the patients in this study eventually discontinued their insulin and controlled it with only perioral medications and an injectable once a week. Conclusion: This study shows that CGM devices can be successfully utilized in a resident-run clinic to improve the management of diabetic patients administering insulin multiple times a day.